Antifungal Potential of Cyanobacterium Nostoc sp. BCAC 1226 Suspension as a Biocontrol Agent Against Phytopathogenic Fungi and Oomycetes - Adele Yusupova; Bakhyt Kartabayeva; Rezeda Sushchenko; Kamilla Gaysina; Prabhaharan Renganathan; Lira A. Gaysina (Applied Microbiology)
Cyanobacteria are gaining significant importance as potential biocontrol agents against phytopathogenic fungi. We evaluated the inhibitory effects of a suspension of Nostoc sp. BCAC 1226 on Penicillium sp., Phytophthora sp., and Stemphylium sp. in vitro using potato dextrose agar medium. On the 7th day of incubation, Phytophthora sp. showed a reduction in colony area from 18.30 ± 1.68 to 8.55 ± 0.74 cm2 (53.6% inhibition). Similarly, Penicillium sp. showed a reduction from 17.64 ± 1.46 to 8.90 ± 0.36 cm2 (49.4% inhibition), and Stemphylium sp. showed a reduction from 17.76 ± 1.28 to 13.5 ± 0.73 cm2 (23.7% inhibition). The inhibitory effects were more significant on the 14th day, with the growth of Phytophthora sp. further reduced to 4.9 ± 0.40 cm2 (72.8% inhibition), Penicillium sp. to 5.54 ± 0.32 cm2 (68.8% inhibition), and Stemphylium sp. to 8.71 ± 0.31 cm2 (50.8% inhibition). These results indicate the potential antifungal activity of Nostoc sp. suspension, with the highest reduction observed in Phytophthora sp., followed by Penicillium sp. and Stemphylium sp. Future research should focus on the chemical characterization of the antifungal metabolites produced by Nostoc sp. BCAC 1226 and in vivo evaluations on economically important crops to evaluate their practical efficiency under field conditions.